Woman between Two Kingdoms : Dara Rasami and the Making of Modern Thailand - Castro-Woodhouse, Leslie, 1968- (Book collections on Project MUSE., 2020)
"A study of Princess Dara Rasami, one of 153 royal consorts to the king of Thailand, that reveals the central roles played by women in the political dynamics of both the nascent Thai nation and Southeast Asia, shedding light on ethnic difference and gender relations in nineteenth- and early-twentieth-century Thailand"--